Status of Flora in Protected Areas the Case Studies of Eight PAs of Madhya Pradesh (India) - Kushwah, R. B. S.; Kumar, V. (Indian Forester, 2002)
The term Biodiversity means the variety and variability among living organisms from all sources and ecosystems on the earth. It includes diversity within species, between species and of ecosystems. Classification is an essential process in our daily lives and a necessary tool for our survival. For example, we need to know which plant, animal, fungi are useful and which are poisonous or dangerous. It is hard to define Biodiversity in mathematical terms. Hence, the ’Biodiversity indices’ are used for the purpose. The Shannon-Wiener Biodiversity Index, based on the proportionate abundance of the species, provides an alternate approach to the assessment of Biodiversity. Attempt has been made for the first time in the eight Pas of Madhya Pradesh, following standard sample techniques and formulae, to compute Biodiversity indices in order to find the present status of flora. The value of Shannon-Wiener Biodiversity Indices and Index of Evenness has been computed. The maximum value (2.505, 2.511) was found for Madhav National Park followed by Satpura National Park. The minimum value (1.717,1.763) was found for Pachmarhi Wildlife Sanctuary. The main recommendations of the study are: (1) Demarcation of the ’Biodiversity zone’ in each Pas and its conservation; (2) The areas with lower Biodiversity indices need to be given more attention for protection and conservation; (3) ’Eco-development planning’ with the active involvement of local people for each PA needs to be adopted along with the village-micro-planning, and (4) The high tourist pressure in PWS, SNP, BNP, RWS and SDS needs to be regulated by ’Eco-tourism planning’ in these PAs.